Design Optimization of DR3AM Vapor Polishing Device for ABS 3D-Printed Parts - Rosa Mae D. Baluyut; Jan Rapaela B. Bartolome; H. Romel B. De Guzman; Josefa L. Morales; Anthony N. Moscosa; Angeline D. Olavides; Jan Aubrey B. Sanchez; Michaela Tayag Espino; Ciara Catherine L. Gache; Brian J. Tuazon; John Ryan C. Dizon (Universitas PGRI Semarang, 2023)
3D printing is an additive manufacturing method that turns digital design into an actual product. A 3D-printed part sometimes requires post-processing to enhance its physical and mechanical properties. Acetone vapor polishing is one of those techniques which is highly beneficial in smoothing ABS 3D-printed parts. Previously, an acetone vapor polishing device has been developed which uses a mist maker. However, for a more efficient polishing method, an optimized vapor polishing device using heat has been fabricated in this study. To assess the efficiency of this device, the researchers test the dimensional accuracy, surface roughness, tensile strength, and impact strength of polished and unpolished ABS 3D-printed specimens. The findings showed that the surface smoothness of the polished cube specimens did not significantly alter its physical geometry. The tensile test reveals that the overall elasticity of the polished tensile specimen has increased significantly while the impact test also shows that the polished specimens have the capacity to sustain a resistive impact from a swinging pendulum. Thus, all testing procedures indicated that post-processing using the optimized vapor polishing device has improved the overall physical and mechanical properties of the polished specimens.